Brief Strategy Family Therapy from Theory to Practice: Generating Evidence through Scientific Articles - Almulhim, Latifah Ahmed (Journal of Educational and Psychological Sciences, 2022)
Brief Strategy Family Therapy (BSFT) is an award-winning, evidence-based program that has been listed by SAMHSA - Substance Abuse and Mental Health Services since 2008. which is used to overcome some behavioral problems such as bullying; Take drugs; socially unacceptable behavior; school truancy. It is an intervention based on a program designed around the effective role of the family to reduce behavioral problems. The main aim of it, is the restructuring of the family and its relations with each other. It is a short-term, structured, and practical approach that addresses the behavioral problems of children and adolescents. Specifically targets children and adolescents between the ages of 6 and 18, who are at risk for behavioral problems, including substance abuse. Its importance is that it is the only model that is strongly categorized into the three categories: mental health insurance; overcoming the problem of drug abuse; Strengthening pedagogical parenting skills at home. While the Arab studies did not address Brief Strategy Family Therapy as an evidence-based program and intervention, to the knowledge of the researcher. The researcher considered it important to review a summary of this intervention, its objectives, steps, and other studies that dealt with Brief Strategic Family Therapy. Noting the extent to which it can be applied in the Kingdom of Saudi Arabia while presenting a vision that puts theoretical information into practice. This is in addition to presenting suggestions that guide future Arab research for the application of Brief Strategic Family Therapy in Kingdom of Saudi Arabia and Arab countries.
Keywords: Emotional or Behavioral Disorders; Brief Strategy Family Therapy; Evidence Based Practices